Persistence of Hyperplastic Primary Vitreous and Cataract in a Dog - Marchionatti Pigatto, Anita; Rech Cassanego, Guilherme; Cauduro da Rosa, Carolina; Iensen Farencena, Fernanda; da Silva Flores, Fabiano; Otavio Eggres Krebs, Carlos; Dutra Côrrea, Luis Felipe (Acta Scientiae Veterinariae, 2023)
Background: Persistent hyperplastic primary vitreous is a rare ocular condition that is usually unilateral, formed when normal regression of the hyaloid vascular system does not occur. Diagnosis is possible through ultrasonography, by obtaining images that provide information and also serve as a differential diagnosis. Clinically the condition presents with signs of leukocoria, microphthalmia, and cataracts, and it can be further classified into 6 degrees according to the evolution. The objective of this work is to describe the case and treatment of a canine of the Pointer breed that presented opacity in both eyes, with diagnosis confirmed through ocular ultrasonography. Case: A 6-year-old male pointer dog, weighing 27 kg, was referred to the Veterinary Medical Teaching Hospital of the Federal University of Santa Maria (UFRGS), Santa Maria, RS - Brazil with a history of blindness. According to the owner, the animal’s right eye has always been “white”, since it was a puppy and the left eye began to present the same characteristic a short time ago. On ophthalmological examination, neither eye showed signs of ocular discomfort, the Schirmer’s tear test was within the range expected for the species, fluorescein and threat tests were negative, and a positive pupillary reflex was observed in the left eye. The right eye had total corneal opacity associated with a chronic lesion and the presence of pigment cells in the medial portion of the eyeball, the opacity making it impossible to visualize the other internal structures of the eyeball. The left eye presented lens opacity. In the ultrasound of the right eye, there were several alterations, the presence of a triangular-shaped hyperechogenic structure in the vitreous chamber, a decrease in the depth of the anterior chamber, and the presence of abnormality in the development of the lens. The findings are compatible with and confirmed the diagnosis of PHPV. In the left eye, the ultrasound images indicated hyperechogenicity of the posterior and anterior poles of the lens, findings compatible with cataracts. Through the animal’s history, complete ophthalmic examination, and use of ocular ultrasonography, it was possible to diagnose and differentiate the causes of the white eye in the patient. The preoperative screening was continued with an electroretinography examination, which showed a satisfactory electrical response for the retina of the left eye and an unsatisfactory electrical response for the retina of the right eye. Phacoemulsification surgery was performed to remove the cataract in the left eye with intraocular lens implantation. The positive threat reflex returned in this eye, with a return of visual acuity. Discussion: Persistent hyperplastic tunica lentis and persistent hyperplastic primary vitreous (PHTVL/PHPV) are congenital anomalies caused by a failure to regress the fetal hyaloid vasculature. These conditions are not common, but occur sporadically in dogs. The PHPV classification can be classified into degrees, based on the morphological aspect of the lesion. Following this classification scheme, the PHPV of the animal in question refers to the 6th degree of evolution. The total opacity of the cornea in the right eye was associated with the presence of a hyperplastic primary vitreous and the leukocoria in the left eye was due to the presence of a mature cataract. The conclusion of the diagnosis was only possible through ocular ultrasonography, which is very useful to differentiate the causes of ocular opacity and leukocoria, in addition to allowing complete evaluation of the intraocular structures and being considered an essential exam to confirm the diagnosis of PHPV. Keywords: hyaloid artery, leukochoria, hyperplastic persistence of the primitive vitreous, ocular ultrasound, pointer. Título: Persistência do vítreo primário hiperplásico e catarata em cão Descritores: artéria hialóide, leucocoria, persistência hiperplásica do vítreo primitivo, pointer, ultrassonografia ocular.